Strategic human resource management - Agarwala, Tanuja (Oxford : Oxford University Press, 2007)
Business
Keywords: Human resource menagement; Human resource environment; Human resource evaluation; Human resource planning; Acquiring human resources; Training and development of HRM; Copensation and rewards management; Managing careers; International HRM; Strategic management; Evolution of HRM